Natural Phenomenon of Twilight in Islamic and Science Perspective - Al Hanani, Moh Lutfi Salim; Rafiah, Jihan Ariqatur; Winarti (Proceeding International Conference on Religion, Science and Education, 2022)
A universe is always process endlessly presents to countless phenomena forever expanding dimensions of space and time. The science explains thats (earth's rotation) on its axis brings with it a degree of darkness to earth’s part and light on the other part. This phenomenon is springed to changes the earth's surface position to the sun's position as a source of light for the earth. We have learned that such as a circumstances are a phenomenon in which is evening and days change. At dusk twilight, is reflected in the eye so that it can be seen and has significant difference in characteristics color and light wavelengths by day and darkness at night. This is pointed focus in Q.S Al Insyiqaq 16 verse thats the twilight is reddish. The study is about integrating a natural phenomenon of twilight in an islamic perspective based on the Qur'an causality and the theorety scientific perspective of the physics in describing twilight. The method is used library research. As for the instruments used in this study are library studies of integrated sources, using descriptive qualitative data analysis. The result of this study is the conclusion that the dusk event mentioned in qur 'an verse with several interpretations of scholars in his works corresponds to a panda.